1997
DOI: 10.1002/(sici)1096-9098(199708)65:4<284::aid-jso11>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

On the growth rates of human malignant tumors: Implications for medical decision making

Abstract: Testicular carcinomas, pediatric tumors, and some mesenchymal tumors are examples of rapidly proliferating cell populations, for which the tumor volume doubling time (TVDT) can be counted in days. Cancers from the breast, prostate, and colon are frequently slow‐growing, displaying a TVDT of months or years. Irrespective of their growth rates, most human tumors have been found: to start from one single cell, to have a long subclinical period, to grow at constant rates for long periods of time, to start to metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
176
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(181 citation statements)
references
References 79 publications
(154 reference statements)
4
176
1
Order By: Relevance
“…2, we consider here the case of prostate cancer, whose specific characteristic parameters are well documented in the literature [18] and have been employed in [19] (10) Assuming for the prostate a metabolic power of 0.2 W (17000 J/day), we find that metastasis starts at a critical time of about two or three weeks after a malignant transformation of the parental tumor. However, since t* depends on P 0 ( ) 1 3 , its dependence on the intrinsic metabolic power of the organ is rather weak.…”
Section: Application To Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…2, we consider here the case of prostate cancer, whose specific characteristic parameters are well documented in the literature [18] and have been employed in [19] (10) Assuming for the prostate a metabolic power of 0.2 W (17000 J/day), we find that metastasis starts at a critical time of about two or three weeks after a malignant transformation of the parental tumor. However, since t* depends on P 0 ( ) 1 3 , its dependence on the intrinsic metabolic power of the organ is rather weak.…”
Section: Application To Prostate Cancermentioning
confidence: 99%
“…corresponding to the preclinical phase, the threshold of clinical diagnostics [18], and the clinical phase where the evolution of the tumor should be studied (since the preclinical evolution is simply a matter of extrapolation).…”
Section: Application To Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…If treatment is delayed the probability of survival may be reduced. 4,7,[10][11][12][13] A limited number of serial pretreatment imaging studies have been undertaken in NSCLC patients who are candidates for potentially curative therapy. In a significant study, O'Rourke and Edwards reported that 21% of 29 candidates for radical RT developed incurable disease progression (median 54 days) between diagnostic/ staging and RT planning computed tomography (CT) scans.…”
mentioning
confidence: 99%
“…15 In a case series of 40 incidentally detected primary solid renal tumors that were monitored with serial CT, most tu- ca: carcinoma. a The three tested incidence rates are those of the U.S. population of ages 60-64 years, 65-69 years, and 70-74 years adjusted for the gender distribution of the study population.…”
Section: Discussionmentioning
confidence: 99%